1939
DOI: 10.1002/lipi.19390460805
|View full text |Cite
|
Sign up to set email alerts
|

Beitrag zur titrimetrischen Wasserbestimmung nach K. Fischer

Abstract: 1. Okaurc: 2. Linolsiure: L = lo/# -( J Z -HhZ) 3. Rizinolsiiure: 4. Dioxystearinsiure: 0 = 0,0978 * HhZ -1,11. J Z -0,56. OHZ -1,992. G + 199,2 H * O,sn43.OHZ+t2,3.15.HhZ+2,11 . G -211 Di = 111,7 -( 1,212 -RhZ + 0,033 -OHZ f 1,117 -G I Auf Grund dieser Oberlegungen wurde ein Rizinusol untersucht, das eine Saurezahl von 0,R hatte und Unverseifhares in einer Menge von 0,35 O / o enthielt. Die mit den notigen VorsichtsmaSregeln daraps isolierten, reinen Fettsauren zeigten folgende Konslanten: sz vz J Z RhZ OHZ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1943
1943
1967
1967

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…which pointed out that the Karl Fischer moisture method applied to ordinary skim or whole milk powders does not include all of the water of crystallization of the lactose. Previously (6), it has been reported that as a result of the insolubility of maltose and lactose in both methanol and the Karl Fischer reagent, these materials can be determined only after preliminary extraction, and when the materials are finely ground. Formamide has been used to replace methanol as the extraction solvent for the determination of moisture in some food products, including cake mixes containing dried milk solids (S, 4).…”
Section: Literature Citedmentioning
confidence: 99%
“…which pointed out that the Karl Fischer moisture method applied to ordinary skim or whole milk powders does not include all of the water of crystallization of the lactose. Previously (6), it has been reported that as a result of the insolubility of maltose and lactose in both methanol and the Karl Fischer reagent, these materials can be determined only after preliminary extraction, and when the materials are finely ground. Formamide has been used to replace methanol as the extraction solvent for the determination of moisture in some food products, including cake mixes containing dried milk solids (S, 4).…”
Section: Literature Citedmentioning
confidence: 99%
“…As no iodine or water is involved in this reaction, no interference is encountered in the titration for water. Zimmerman (35) published the data on aqueous hydrogen peroxide solutions shown in Table VI. Dialkyl peroxides are relatively stable and do not oxidize hydrogen iodide at a sufficient rate to offer any interference in the titration for water.…”
Section: Rooh+soj-rhso (11)mentioning
confidence: 99%